2020
DOI: 10.1186/s13063-020-04475-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial comparing efficacy and safety of high versus low Low-Molecular Weight Heparin dosages in hospitalized patients with severe COVID-19 pneumonia and coagulopathy not requiring invasive mechanical ventilation (COVID-19 HD): a structured summary of a study protocol

Abstract: Objectives: To assess whether high doses of Low Molecular Weight Heparin (LMWH) (i.e. Enoxaparin 70 IU/kg twice daily) compared to standard prophylactic dose (i.e., Enoxaparin 4000 IU once day), in hospitalized patients with COVID19 not requiring Invasive Mechanical Ventilation [IMV], are: a) more effective in preventing clinical worsening, defined as the occurrence of at least one of the following events, whichever comes first: 1. Death 2. Acute Myocardial Infarction [AMI] 3. Objectively confirmed, symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…In the literature there are no high-quality data yet supporting early use of LMWH at a therapeutic dose in patients with COVID-19, outside the setting of VTE treatment; randomized controlled studies evaluating this question are planned [ 23 ] or open to recruitment ( NCT04362085 , NCT04345848 , NCT04359277 ) or performed in a low number of patients [ 24 ]. In a French study conducted by Llitjos et al [ 24 ] in which there were included 26 critically ill patients with severe COVID-19 pneumonia, the anticoagulation dose (prophylactic or therapeutic) was chosen at the discretion of the treating physician based on the individual risk of thrombosis; the authors found no difference within groups, suggesting that therapeutic dose could be unjustified.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are no high-quality data yet supporting early use of LMWH at a therapeutic dose in patients with COVID-19, outside the setting of VTE treatment; randomized controlled studies evaluating this question are planned [ 23 ] or open to recruitment ( NCT04362085 , NCT04345848 , NCT04359277 ) or performed in a low number of patients [ 24 ]. In a French study conducted by Llitjos et al [ 24 ] in which there were included 26 critically ill patients with severe COVID-19 pneumonia, the anticoagulation dose (prophylactic or therapeutic) was chosen at the discretion of the treating physician based on the individual risk of thrombosis; the authors found no difference within groups, suggesting that therapeutic dose could be unjustified.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, patients on prophylactic anticoagulation had higher venous thromboembolism than the therapeutic anticoagulant arm, although the latter group had a higher overall incidence of thromboembolic events, including pulmonary embolism (131). It is envisaged that these issues will be answered in ongoing clinical trials, such as the COVID-19 HD, a randomized controlled trial comparing high-dose vs. low-dose LMWH (132).…”
Section: Prophylaxis and Management Of Thromboembolism In Covid-19mentioning
confidence: 99%
“…Although there is a recognized association between COVID-19 and coagulopathy, and the disease score severity is positively correlated with pro-coagulant markers (e.g., high D-dimer and fibrinogen levels), accurate risk–benefit evaluations should be considered particularly in severe COVID-19 patients. Indiscriminate anticoagulants administration may increase the risk of spontaneous hemorrhage, heparin-induced thrombocytopenia (HITP) and anti-PF4-heparin complex antibodies formation [ 46 , 47 , 48 , 49 , 50 ]. Finally, in addition to the kind of heparin used for patients’ treatment (i.e., LMWH versus HMWH), individual bleeding and thrombotic risk should be considered both during hospitalization and in post-discharge COVID-19 patients [ 51 , 52 ].…”
Section: Ace1/ace2 Balancementioning
confidence: 99%